Equine doping: perceptions, adverse effects and Cyprus hippodrome case review for the years 2001-2010 - SPANOUDES (Κ. ΣΠΑΝΟΥΔΗΣ) K.; DIAKAKIS (Ν. ΔΙΑΚΑΚΗΣ) N. (Journal of the Hellenic Veterinary Medical Society, 2017)
Doping in race horses affects thousands of equine athletes worldwide. Illicit administration of medical compounds aims to improve the horse’s performance either through altering the athletic capacity, or through covering the symptoms of pathologic conditions. Nicosia race track has a significant number of confirmed doping cases when considering the small equine population of the island, reflecting the lack of credibility of racing in Cyprus. The most frequently administered medications are anabolic steroids, human recombinant erythropoietin, stimulants, diuretics, non-steroidal anti-inflammatory drugs, local anesthetics, bronchodilators and coagulants. Interestingly, published literature on the effectiveness of these substances is inconclusive or contradictory. This article constitutes a cumulative presentation of confirmed doping cases in Nicosia race track and a brief review on the published literature regarding the effectiveness of the most commonly administered compounds.